Dochody z cła w systemie budżetu państwa - Skłodowski, Maciej (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 2010)
In the article the level of budget incomes from customs duty in Poland after accession to the European Union is presented. It is outlined the degradation of their importance as the national budget earnings as well as their important role as a part of the membership fee to the EU making “traditional own resources” (TOR). The article presents the activities of the Customs Authority, that got new objectives relating to collection of customs and tax receivables’ forming over 1/3 of state budget’s incomes. It is determined, that the main factor increasing the earnings from customs duty is the restriction of government’s bureaucratic barriers in the national and international turnover that leads to the increase of the competitiveness of the polish customs system, encouraging the entrepreneurs to carry out custom clearances on the territory of Poland.